Learning in deprivation - Quader, Dil Afroze (Dhaka, Bangladesh : University Press, 1993)
Study conducted on the Bangladeshi school students in the United Kingdom.
Includes bibliographical references (pages [154]-163).
BIED
Keywords: Bangladeshis -- Education (Secondary) -- England -- London -- Case studies; English language -- Study and teaching (Secondary) -- England -- London -- Bengali speakers -- Case studies; Education; Second language acquisition -- Case studies